1961
DOI: 10.4319/lo.1961.6.2.0175
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Amino Acids by Marine Invertebrates1

Abstract: The capacity for removal of amino acids from solution by marine animals was studied by following the concentration of an acid added to the ambient sea water. Thirty‐five genera representing 11 phyla were examined. The representatives of 10 of the phyla removed significant quantities of glycine from solution during an observation period of from 16 to 24 hr. This capacity for uptake of glycine was not limited to filter‐feeding animals. Observations using representatives of 3 phyla and various amino acids indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(58 citation statements)
references
References 9 publications
3
55
0
Order By: Relevance
“…Hesionides arenana and the genus Trilobodnlus have a relatively thin cuticle penetrated by numerous microvilli (Westheide and Rieger, 1978;Rieger and Rieger, 1976). Dense cuticular layers, however, inhibit or impede nutrient transport in Crustacea and Chelicerata (Stephens and Schinske, 1961). Our few experiments conducted with the copepod Rhizothrix gracilis confirm this.…”
Section: Discussionsupporting
confidence: 69%
“…Hesionides arenana and the genus Trilobodnlus have a relatively thin cuticle penetrated by numerous microvilli (Westheide and Rieger, 1978;Rieger and Rieger, 1976). Dense cuticular layers, however, inhibit or impede nutrient transport in Crustacea and Chelicerata (Stephens and Schinske, 1961). Our few experiments conducted with the copepod Rhizothrix gracilis confirm this.…”
Section: Discussionsupporting
confidence: 69%
“…The experimental treatments used were FSW, UV-irradi ated seawater (UVSW), UVSW enriched with 1 �M each of alanine, aspartic acid, glucose and glycine (Mixture), and UVSW enriched with 1 �M of Palmitic acid. Alanine, aspartic acid, glucose, glycine and PA were selected for DOM enrichment based on previous studies that found each of these compounds to be read ily transported by various animals (e.g., Stephens and Schinske 1961;Stephens 1962;Shick 1975;Ferguson 1980b;Manahan et al 1982;Manahan 1983;Jaeckle and Manahan 1989;Jaeckle 1994Jaeckle , 1995. The concen trations utilized were based on concentrations natu rally occurring in surface water (Benner 2003).…”
Section: Performance Comparisonsmentioning
confidence: 99%
“…A seminal study conducted by Stephens and Schinske (1961) found via colorimetric observation that animals representing ten phyla removed signiWcant quantities of glycine from solution. Although this uptake occurred using glycine concentrations far exceeding those found naturally (approximately 2 mM), Stephens (1962) fur ther showed the appearance of radiolabeled glucose within the solitary coral Fungia scutaria in concentra tions as low as 5.5 �M.…”
Section: Introductionmentioning
confidence: 99%
“…Stephens & Schinske 1961, Ferguson 1967, Davis & Stephens 1984, Manahan 1989. There is also a smaller body of literature that shows invertebrates can transport other classes of compounds such as sugars (e.g.…”
Section: Introductionmentioning
confidence: 99%